The GP’s a stranger: an interpretive phenomenological analysis exploring patient experiences of changed access to primary care in the management of long-term conditions - Walker, Sandra; Daniel, Tansy; Yildizcan, Mediha; Roddis, Jennifer Karen (Frontiers in Health Services, 2025)
IntroductionSelf-management is promoted as a mechanism for those with long-term health conditions to manage their condition day-to-day. Changes in access to primary care in the UK have led to an increased patient burden and reduced access to care.MethodsThis exploratory study considered the impact of such changes for those managing long term physical and mental health conditions. An interpretative phenomenological analysis approach was adopted. Interviews were conducted with eight individuals affected by long-term physical and/or mental health conditions.ResultsOne overarching superordinate theme was identified as significant to all participants: The GP's a stranger. This superordinate theme was fundamental to five lower order themes: Role of GP; Fighting to gain access; Dismissed, depersonalised and devalued; Resourcefulness borne of desperation, and “There was something wrong”, which offered insights into the experiences of participants.DiscussionThose living with long-term conditions often know when they need to seek additional healthcare support however they shared multiple barriers to accessing this support when needed and reported that the lack of relationship with any health care professional in primary care affected their ability to trust any care advice they were given. Considerations of a new way of operating within a changed paradigm of primary care are explored.